(Invited) Metallic Nanocoatings on Optical Fibers as a Sensor Platform. (10th September 2015) - Mandia, David J.; Zhou, Wenjun; Wells, Adam; Albert, Jacques; Barry, Sean Thomas
Abstract : Deposition of gold metal on a tilted fiber Bragg grating (TFBG) demonstrates the utility of this optical fiber as a sensor for the conditions at the fiber's surface, including the continuity of a deposited metal film. Two precursors for the deposition of metallic gold are contrasted: gold(I) N'N'-dimethyl N, N"-diisopropylguanidinate (1) and gold(I) tert-butyl-imino-2, 2-dimethylpyrrolidinate (2). Characterization of the deposition by optical fiber spectroscopy highlights the difference in thermal stability and growth rate of these two compounds. Compound 1 has a tremendous growth rate (220 nm/min) but is very thermally unstable, while 2 is much more thermally stable, and shows a lower growth rate of 1 nm/min.